Observation of Influence of Nucleons＇ Motion on Kaons Collective Flow in Dense Medium - 邢永忠 郑玉明 王艳艳 张林 屈世显 (Chinese physics letters, 2010)
In order to extract the information of the momentum-dependent interaction of kaons under the extreme condition, the properties of the positively charged kaons produced in a heavy ion collision are studied via a simple model which has an invariable nucleon＇s velocity. Our special attention is focused on the observation of the dependence of the kaon＇s properties on the motion of nucleons in a hot and dense nuclear environment. Starting from two kinds of kaon quasiparticle models defined in transport theories for simulating heavy ion collisions, we calculate the effective mass and potential of the K＋＇s produced in the collisions and find that these properties not only depend closely on the velocity of nucleons but the dependence varies with kaon＇s quasiparticle model. It is clearly shown that the motion of nucleons reduces the momentum of K＋＇s at a given rapidity and thus weakens the rapidity distribution of K＋＇s directed flow in realistic nuclear collisions.